Desulfurization of molten steel with molten slag using the electrochemical method - Wu X.-Q.; Xu J.-F.; Gu P.-W.; Zhang J.-Y. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The desulfurization in metallurgical process is electrochemical reaction in nature. Desulfurization using the electrochemical method was proposed with the CaO-MgO-Al2O3 molten slag covering molten steel. Effect of an applied external DC voltage, which varied from 0 to 8V, was discussed. The results indicated that sulfur in molten steel could be removed effectively with applied external voltage. According to the mechanism analyses of the desulfurization under the applied external voltage, kinetics formulae were developed, and the model calculated results that were in agreement with the experimental values. The transfer coefficient of sulfur in molten slag under electromigration conditions was approximately 2.09×10-5 m·s-1·V-1. The desulfurization of molten steel with molten slag can be promoted by increasing the applied voltage, reducing the partial pressure of atmospheric oxygen, strengthening the stirring intensity of the reaction system, and optimizing the composition and properties of the slag.